The Burda Poem And The Research, Writings And Oppositions Surrounding It/ قصيدة البردة وما دار حولها من الشروح والتأليفات - Alhajj Ebrahim, Abdullah Omar; Al-Zahranmi, Mohammed Jarallah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The Arabic literary heritage is rich and full of stories, tales, anecdotes, poems, and everything that appeals to human taste. This heritage includes many famous and remarkable poems. Classical literary collections—such as Hamasat (an enthusiastic collection of poems), Amali (dictations), and others—contain many of these poems and literature. Some of these poems have received significant attention from scholars who have studied and analyzed them. Among the most famous is the poem